The Effectiveness of Self Management Techniques to Reduce Academic Procrastination Behavior of Grade VIII Students at SMP Negeri 1 Tinambung - Nadia Mutiara (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
Students often encounter various obstacles when achieving their best quality, one of which is academic procrastination behavior. This study aims to examine the effectiveness of self-management techniques in reducing academic procrastination among eighth-grade students at SMP Negeri 1 Tinambung. Academic procrastination is recognized as a major barrier to student achievement, characterized by habitual delays in task completion. The research employed a quasi-experimental method with a pretest-posttest control group design. Data were collected using a Likert-scale questionnaire administered before and after the intervention. The participants consisted of 30 students identified as having high levels of academic procrastination. The findings revealed a significant reduction in procrastination behavior following the group counseling sessions incorporating self-management techniques. These results confirm that self-management is an effective approach to enhancing students' time management and academic responsibili. .